NTCETLS: A Novel Technique For Cryptography Ensuring Two Level Security - Ghosh, Sourav; Das, Prithwijit; Nath, Ira; Singh, Dharmpal; Sahana, Sudipta (International Journal of Computer Sciences and Engineering, 2020)
The method of hiding a message so that only the actual recipient receives it properly and securely is referred as encryption. Encryption can contribute a technique for hiding data from intruders. As huge amount of data is stored on computers or transmitted via computers are exposed to the attackers which is at a risk. With the quick evolution of digital information transmission in electronic way, data safety is essential in information storage and transmission. The confidentiality of data has a remarkable role in various fields like ethics, law and currently in Data Systems. With the progress of human intelligence, the art of cryptography has grown to be more complicated with the aim of make data more safe and secure. Different collections of Encryption systems are being utilized in the world of Data Systems by different institutes. A new algorithm has been proposed for the security purpose of the data to be hidden from any unauthorized access. The proposed algorithm takes a 4-digit user-defined key and also generates a key which will be used to decrypt the same. The new technique is able to handle any size data efficiently and effectively for cryptography. We have used two layers cryptography technique which is totally new as far of our knowledge. It can provide more security of data than existing works in linear time.